Analyzing the Efficiency of Travel and Tourism in the European Union - Barisic, Petra; Cvetkoska, Violeta (Springer, 2020)
As one of the world’s largest and growing economic sectors, travel and tourism significantly contributes to GDP, creates jobs, drives exports, and generates prosperity across the world. Therefore, it is essential to know which countries successfully manage their travel and tourism , and can serve as an example for the others. The aim of the paper is to analyze the efficiency of travel and tourism impact on the GDP and employment in the European Union at the macro level, by using the nonparametric approach data envelopment analysis . All 28 member states of the European Union were included in the research. The observation period was one year (2017). Two inputs and two outputs were selected. Internal travel and tourism consumption and capital investment were the inputs, while travel and tourism’s total contribution to GDP and employment were the outputs. The obtained results are presented, interpreted and there are recommendations given for the tourism policy-makers regarding making better decisions.
Keywords: operational research; DEA; decision-making unit; efficiency analysis; European union; travel and tourism